The emerging role of BET inhibitors in breast cancer - Angeliki Andrikopoulou; Michalis Liontos; Konstantinos Koutsoukos; Meletios-Athanasios Dimopoulos; Flora Zagouri (Breast, 2020)
Bromodomain and extraterminal domain (BET) proteins are epigenetic molecules that regulate the expression of multiple genes involved in carcinogenesis. Breast cancer is an heterogenous disease emerging from aberrant gene expression and epigenetic alteration patterns. Amplification or overexpression of BET proteins has been identified in breast tumors highlighting their clinical significance. Development of BET inhibitors that disrupt BET protein binding to acetylated lysine residues of chromatin and suppress transcription of various oncogenes has shown promising results in breast cancer cells and xenograft models. Currently, Phase I/II clinical trials explore safety and efficacy of BET inhibitors in solid tumors and breast cancer. Treatment-emergent toxicities have been reported, including thrombocytopenia and gastrointestinal disorders. Preliminary results demonstrated greater response rates to BET inhibitors in combination with already approved anticancer agents. Consistently, BET inhibition sensitized breast tumors to chemotherapy drugs, hormone therapy and PI3K inhibitors in vitro. This article aims to review all existing preclinical and clinical evidence regarding BET inhibitors in breast cancer.